CRISPR-mediated Integration of Large Gene Cassettes using AAV Donor Vectors - Bak, Rasmus O. (Cell Rep, 2017)
The CRISPR/Cas9 system has recently been shown to facilitate high levels of precise genome editing using adeno associated viral (AAV) vectors to serve as donor template DNA during homologous recombination (HR). However, the maximum AAV packaging capacity of ~4.5 kilobases limits the donor size. Here we overcome this constraint by showing that two co-transduced AAV vectors can serve as donors during consecutive HR events for integration of large transgenes. Importantly, the method involves a single-step procedure applicable to primary cells with relevance to therapeutic genome editing. We use the methodology in primary human T cells and CD34(+) hematopoietic stem and progenitor cells to site-specifically integrate an expression cassette that as a single donor vector would otherwise amount to a total of 6.5 kilobases. This approach now provides an efficient way to integrate large transgene cassettes into the genomes of primary human cells using HR-mediated genome editing with AAV vectors.